The Crisis of Globalization and Sustainability - Mazumdar, Surajit (KnE Social Sciences, 2024)
This research aims to analyze the extent of the globalization crisis and its impact on sustainability. This study uses content analysis method to analyze various documents, such as reports, articles, or policies, to identify patterns, themes, and trends related to globalization and sustainability crises. The research results indicate that the globalization crisis is a paradoxical consequence of the globalization process itself. Although economic integration has connected the world, it has not created the basis for their integration as a human collective capable of acting together, toward common goals. In every country, growing disparities raise questions about sustainability, with debate over sharing the burden between developed and developing countries. To achieve a more equal global order, countries must be able to cooperate and accept each other as equal partners, not in competition. Keywords: crisis, economic integration, globalization, sustainability